Ten-year thematic review and future trends of green warehouse - Azian, Ibrahim; Fernando, Yudi (Inderscience Enterprises Ltd., 2023)
In today’s business environment, the study of green warehouses has become a popular topic among industry practitioners and scholars. A green warehouse has frequently been referred to as one of the solutions for warehouse sustainability. In order to meet the environmental demands of stakeholders to reduce environmental pollution and ensure societal safety, some firms have incorporated several sustainable practices into their warehousing activities, resulting in the formation of green warehouse management. Despite its popularity, there is a lack of existing studies which discuss the current trends of green warehousing. Therefore, this paper aims to explore current trends in green warehouses from 2012 to 2022 using ATLAS.ti 9. A list of keywords that are related to this scope of research was identified. In the second step, the keywords were used to locate Potentially relevant papers using Scopus, Science Direct, and Google Scholar, and a total of 31 papers were reviewed. A themed review was carried out, where 12 themes were identified. The results suggest a new framework of research trends for green warehouses. This study will benefit future studies that focus on green warehouse best practices.